CHARTIER, Roger. O que é um autor? Revisão de uma genealogia. Tradução de Luzmara Curcino; Carlos Eduardo de Oliveira Bezerra. São Carlos: EdUFSCar, 2012. 90 p. - TAVARES, MARIANA RODRIGUES (Outros Tempos: Pesquisa em Foco - História, 2014)
Boa leitura!